KAPASITAS SEBAGAI SISTEM PRODUKSI - PURYANDANI, SITI (STIE Totalwin Semarang, 2011)
Strategic capacity involves an investment decision that must match resource capabilities to a long term demand forecast. This paper explain factors to be taken into account in selecting capapcity additions for both manufacturing and service include : the likely effects of economies of scale, the effects of experience curve, the impact of changing facility focus and balance among production stages and the degree of flexibility of facilities and the workforce. Â